Implementasi Metode Tāsmiʿ dalam Menjaga Kualitas Hafalan Al-Qur’an Santri Putri Bait Tāḥfiẓh Al-Qur’an - Fard, Haqiki Fanmaddamkhul; Mujab, M.; Sholeh, Ahmad (DIMAR: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the application of the tāsmiʿ method in maintaining the quality of Qur'an memorization among female students of Bait Tāḥfiẓh al-Qur'an (BTQ). BTQ students are active students from various departments who are required to memorize at least 3 juz per year, participate in dormitory activities, and participate in the ma'had program. The main challenges faced by the students include difficulty in dividing time for muraja'ah, lack of enthusiasm, and decreased motivation in maintaining memorization. This study employs a descriptive qualitative approach, utilizing data collection techniques that include observation, in-depth interviews with dormitory heads, administrators, and BTQ members, as well as documentation. The results of the study indicate that the tāsmiʿ method, which is applied routinely, both in the form of individual deposits and group muraja'ah, is effective in maintaining the quality of students' memorization. These activities include daily halaqah, deposits to teachers, partner-an, monthly tasmi’ khatmil, and personal strategies such as repeating memorization every day, marking verses that are often forgotten, and finding muraja’ah friends. The application of this method helps correct reading errors, improve concentration, and strengthen memorization. Students who are consistent show better memorization quality and self-confidence when submitting memorization. Although effective, the implementation of this method still needs improvement so that the results are more optimal.